Transformation of Classical Tectonics in St. Sophia of Constantinople and Its Reflection in Byzantine Descriptions - Zakharova, Anna V. (Actual Problems of Theory and History of Art, 2017)
The aim of this article is twofold: firstly, to analyze the main architectural devices used to embody St. Sophia’s spiritual contents; secondly, to understand how they were realized and reflected in Byzantine ekphraseis of the building. Analyzing the formal qualities of St. Sophia’s interior, we would like to single out some features that seem essential. The first one is St. Sophia’s special composition uniting axial and centripetal movements intensified through its unique vaulting system. This engenders an impression of spatial forms being in constant self-generated motion. The predominance of the dome determines another significant peculiarity of St. Sophia’s interior: its atectonic quality. All other forms are perceived as derivatives from the dome. Therefore, the descending movement prevails over the ascending; hovering curvilinear forms dominate over clear-cut relations between vertical and horizontal elements. The third essential quality of St. Sophia is its extraordinary luminosity due to the thinness of walls, great number of windows, shimmering of marble revetment and golden mosaic. Transforming the main principles of classical tectonics allowed the architects to imbue the church interior with an irrational quality creating the impression of Divine presence. Analyzing the ekphraseis of St. Sophia by Procopius of Caesarea (6th century), Paul the Silentiary (6th century) and Michael the Deacon (12th century), we follow the same lines of inquiry. How do these authors perceive the spatial layout of the church? What is their reaction to the transformation of classical tectonics? How do they asses the role of light? What is their overall impression and interpretation of the building? Our research has shown that St. Sophia’s contemporaries, Procopius and Paul, demonstrate deep penetration into the architects’ intentions. Michael the Deacon shows a different perception of architecture which is more abstract. Yet all the three ekphraseis clearly express the main idea which is congenial to that of the architects: the impression of Divine presence in the church and supernatural beauty and grandeur corresponding to it.
Keywords: Byzantine architecture; Saint Sophia of Constantinople; Byzantine ekphrasis; Procopius of Caesarea; Paul the Silentiary; Michael the Deacon